2006
DOI: 10.11606/issn.2176-7262.v39i1p39-50
|View full text |Cite
|
Sign up to set email alerts
|

Ratos Espontaneamente Hipertensos E Neuropatias Periféricas

Abstract: Fazan VPS, Kalil ALR, Alcântara ACL, Genari AB, Tavares MR, Rodrigues AR, Salgado HC. Ratos espontaneamente hipertensos e neuropatias periféricas. Medicina (Ribeirão Preto) 2006; 39 (1): 39-50.Resumo: Modelo do Estudo: O presente estudo é uma revisão de literatura sobre o modelo de hipertensão espontânea e as conseqüências da hipertensão para o sistema nervoso periférico, somático e autonômico.Importância do problema: Hipertensão é o principal fator de risco para acidente vascular cerebral e demência vascular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
0
3
0
1
Order By: Relevance
“…Regarding cardiovascular parameters, AP was increased in all groups at 30 and 60 days of protocol when compared to their initial values at 7 and 15 days. Fazan et al [23] have observed that SHR begin to develop hypertension at 5 weeks of age. In the present study, fructose consumption induced an additional increase in AP at 60 days of protocol when compared to the control group in the same period.…”
Section: Plos Onementioning
confidence: 99%
“…Regarding cardiovascular parameters, AP was increased in all groups at 30 and 60 days of protocol when compared to their initial values at 7 and 15 days. Fazan et al [23] have observed that SHR begin to develop hypertension at 5 weeks of age. In the present study, fructose consumption induced an additional increase in AP at 60 days of protocol when compared to the control group in the same period.…”
Section: Plos Onementioning
confidence: 99%
“…In 1963, Okamoto and Aoki developed an experimental model to study hypertension, which diff ered from others as it does not require pharmacological or surgical interventions [13]. In this model, animals were genetically selected by genetic inbreeding.…”
Section: Genetic Hypertensionmentioning
confidence: 99%
“…Test animals develop hypertension at week fi ve and the values to be considered as spontaneous hypertension are between the seventh and 15 th week, the plateau occurs between week 20 and 28 [16]. It was observed in this model that the increase in heart rate is prior to the elevation of systolic blood pressure [13].…”
Section: Genetic Hypertensionmentioning
confidence: 99%
“…Além de ser a causa evitável mais importante de doenças cardíacas e acidentes vasculares cerebrais em todo o mundo, estudos clínicos em pacientes hipertensos demonstraram que a pressão arterial elevada tem sido associada à redução da densidade mineral óssea e consequentemente a um risco aumentado de fraturas (HONG et al, 2019;TSUDA;NISHIO;MASUYAMA, 2001;CAPPUCCIO et al, 1999). A HA leva ao baixo turnover ósseo, o que pode ser um dos mecanismos da redução na massa óssea cortical e trabecular relacionada à esta doença (HU et al, 2021;BASTOS et al, 2010;FAZAN et al, 2006;WANG et al, 1993;BARBAGALLO et al, 1991;IZAWA et al, 1985).…”
Section: Those Were the Best Days Of My Life!"unclassified